2009
DOI: 10.1182/blood.v114.22.1138.1138
|View full text |Cite
|
Sign up to set email alerts
|

MICA-129 Genotype, Soluble MICA and Anti-MICA Antibodies as Biomarkers of Chronic Graft Versus Host Disease.

Abstract: 1138 Poster Board I-160 Background The MHC class I-related chain A (MICA) molecules is of particular in non T-cell receptor (TCR)-mediated immune function. MICA engages NKG2D, a C-type lectin expressed on effector cells including NK, and T cells. Such engagement triggers NK cells and co-simulates T lymphocytes to mount adequate immune response. Further, a soluble isoform of MICA (sMICA) has been implicated in the pathogenesis of a variety of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(55 citation statements)
references
References 0 publications
2
45
0
8
Order By: Relevance
“…In HSCT, MICA allo-antigens may represent a novel transplantation antigen, Parmar et al noticed higher rates of aGVHD in MICA mismatched patients irrespective of HLA matching (32). Other investigators showed similar effects of MICA mismatching in worsening of aGVHD (31,41). Kitcharoen et al noticed improved survival in MICA-matched donor-recipient pairs (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HSCT, MICA allo-antigens may represent a novel transplantation antigen, Parmar et al noticed higher rates of aGVHD in MICA mismatched patients irrespective of HLA matching (32). Other investigators showed similar effects of MICA mismatching in worsening of aGVHD (31,41). Kitcharoen et al noticed improved survival in MICA-matched donor-recipient pairs (42).…”
Section: Discussionmentioning
confidence: 99%
“…In renal (24,25), lung (26,27), heart (28,29) and liver (30) transplantation, recent reports identified posttransplantation MICA antibody development as a risk factor for allograft rejection. In HSCT these alloantibodies are described as an independent risk factor for development of acute and chronic GVHD (graft vs host disease) (31,32). Therefore, in this exploratory retrospective study, we have investigated alloimmunization against HLA and MICA antigens by microparticle-based flow cytometry technology following GT to address their role for outcome in HSCT patients requiring GT during clinical course.…”
Section: Introductionmentioning
confidence: 99%
“…The MICA allele group 129val (alleles 004/005/006/008/ 009/013/016/019/022/024/027/028/033/044/048/049/053/054/ 056/057/058) is characterized by an amino acid substitution at pos 129 (M → V, methionine → valine) which has been shown to significantly reduce binding affinity to the NKG2D receptor in vitro (20). Till date, the functional relevance of this polymorphism has been marginally investigated (21).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of graft versus host disease (GvHD) has been shown to increase in cases of HSCT matching HLA genotypes and mismatched MICA genotypes (6). MICA-129val was shown to be correlated with susceptible chronic GvHD in a French study (7). In addition, MICA-129met has been associated with susceptible early onset ankylosing spondylitis in Algerians (8).…”
mentioning
confidence: 99%